x2 + x - 12 = 0

Question

Asked 6/19/2013 11:33:55 AM

Updated 9/11/2017 5:11:50 AM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by alfred123 [9/11/2017 5:11:50 AM]

andrewpallarca|Points 22594|

Question

Asked 6/19/2013 11:33:55 AM

Updated 9/11/2017 5:11:50 AM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by alfred123 [9/11/2017 5:11:50 AM]

Rating

3

x^2 + x - 12 = 0

(x - 3)(x + 4) = 0;

x - 3 = 0;

x = 3

x + 4 = 0;

x = -4;

x = -4, x = 3

(x - 3)(x + 4) = 0;

x - 3 = 0;

x = 3

x + 4 = 0;

x = -4;

x = -4, x = 3

Added 9/11/2017 5:11:41 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [9/11/2017 5:54:15 AM]

Find the GCF of the given polynomial User: Find the GCF of the given polynomial 16a4b4 + 32a3b5 - 48a2b6
**Weegy:** 16a2b4 **User:** Find the GCF of the following literal terms m7n4p3 and mn12p5
**Weegy:** m7n12p3 **User:** Simplify p(p - q) - q(q - p).
**Weegy:** b(a + b) - a(a - b) is equal to n^2-a^2+2ab or -a^2+2ab+b^2. SOLUTION: b(a + b) - a(a - b) ab+b^2-a^2+ab b^2-a^2+ab+ab n^2-a^2+2ab or -a^2+2ab+b^2 **User:** Find the product
-7(8 + k)
**Weegy:** I think your equation is incomplete. **User:** 4x 3 y 2(7xy 4)
(More)

Question

Updated 6/25/2014 3:17:15 AM

4 Answers/Comments

The GCF of m^7n^4p^3 and mn^12p^5 is mn^4p^3.

Added 6/25/2014 3:15:23 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [6/25/2014 8:14:59 AM]

p(p - q) - q(q - p)

= p^2 - pq - q^2 + pq

= p^2 - q^2

= p^2 - pq - q^2 + pq

= p^2 - q^2

Added 6/25/2014 3:16:16 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [6/25/2014 8:15:11 AM]

-7(8 + k) = -56 - 7k

Added 6/25/2014 3:16:42 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [6/25/2014 8:15:32 AM]

Score:
Describe the following sequence as arithmetic, geometric or neither.
2, 4, 6, 12, 14. . . .

Question

Updated 1/6/2015 4:27:44 AM

1 Answer/Comment

The following sequence 2, 4, 6, 12, 14. . .is neither arithmetic nor geometric , it has not common difference or common ratio .

Added 1/6/2015 4:27:44 AM

This answer has been confirmed as correct and helpful.

Confirmed by sujaysen [1/6/2015 6:58:41 AM]

Score:
The line of symmetry for the quadratic equation y = ax 2 - 8x - 3 is x = 2. What is the value of "a"?
**Weegy:** answer: x= -5. (More)

Question

Updated 1/6/2015 7:36:23 PM

1 Answer/Comment

The line of symmetry for the quadratic equation y = ax^2 - 8x - 3 is x = 2. 2 is the value of "a" .

8/2a = 2

4a = 8

a = 8/4

a = 2

8/2a = 2

4a = 8

a = 8/4

a = 2

Added 1/6/2015 7:36:23 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [1/6/2015 11:49:20 PM]

The following sentence has a participle.
After an hour in the movie theater, the crying woman finally left to go blow her nose.
True
False **Weegy:** False. The sentence "After an hour in the movie theater, the crying woman finally left to go blow her nose." does not contain a participle. (More)

Question

Expert Answered

Updated 2/24/2014 2:11:19 PM

1 Answer/Comment

After an hour in the movie theater, the crying woman finally left to go blow her nose. It's TRUE that this sentence contains a participle: CRYING (that modifies the woman).

Added 2/24/2014 2:11:18 PM

This answer has been confirmed as correct and helpful.

Find the product.
2y 2(3x + 5z)
User: Find the product.
2y^2(3x + 5z)
User: Find the product.
-a 2b 2c 2(a + b - c)
**Weegy:** The answer is -8abc(a+b-c) **User:** Simplify (8m - 4n) + (6m + 3n).
**Weegy:** (8m - 4n) (6m 3n). What is the operation between 6m and 3n? **User:** Find the product.
a 4(3a 2 - 2a + 1)
**Weegy:** The answer for a^2 + 5a - 3a^2 is 5 a-2 a^2.
(More)

Question

Updated 5/30/2014 9:01:57 AM

3 Answers/Comments

2y^2(3x + 5z) = 6xy^2 + 10y^2z

Added 5/30/2014 9:00:47 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [5/30/2014 9:02:58 AM]

(8m - 4n) + (6m + 3n)

= 8m - 4n + 6m + 3n

= 14m - n

= 8m - 4n + 6m + 3n

= 14m - n

Added 5/30/2014 9:01:22 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [5/30/2014 9:03:16 AM]

a^4(3a^2 - 2a + 1) = 3a^6 - 2a^5 + a^4

Added 5/30/2014 9:01:57 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [5/30/2014 9:03:34 AM]

30,137,362

questions answered

There are no comments.